Repeated injections of isovaline lead to analgesic tolerance and cross-tolerance to salicylate but not to morphine in male mice - Moghimian, Maryam; Nazari-Motlagh, Reza; Alavi-Kakhki, Seyed Sajjad; Ghaffari, Mahdi Khorsand; Akbari, Elham; Fani, Masoumeh; Sadegh, Mehdi; Gholami, Masoumeh (Drug Research, 2025)
Tolerance to the antinociceptive effects of opioids is a major concern. Studies have shown that chronic use of non-steroidal anti-inflammatory (NSAIDs) causes significant tolerance and cross-tolerance to morphine. Chronic NSAIDs use can increase the risk of certain diseases, such as peptic ulcers, and exacerbate others, like heart failure. Therefore, developing novel pharmacological approaches could provide considerable benefits for chronic therapeutic procedures. Isovaline with a chemical structure similar to glycine and GABA induce a significant analgesic effect through GABA-B receptors. In this study, we investigated the impact of both short-term and long-term use of isovaline on the immediate response to pain, as well as the development of analgesic tolerance through daily injection (i.p.) of isovaline (100 mg/kg) for 5 days in male Balb/c mice. Additionally, on day 6, we examined the potential for cross-tolerance between isovaline and sodium salicylate (300 mg/kg) or morphine (5 mg/kg). The findings showed that isovaline injection resulted in a delayed onset of analgesic effect, a lowered peak effect, and less cumulative pain relief compared with sodium salicylate and morphine. This analgesic effect gradually decreased over the five days of isovaline injection. When sodium salicylate was injected into isovaline-tolerant mice, the antinociceptive effect decreased, suggesting cross-tolerance to sodium salicylate. However, no such tolerance was observed following morphine injection. Accordingly, it seems that chronic isovaline may interact with the sodium salicylate analgesic pathway but not with morphine.
Keywords: anti-nociception; morphine; salicylate; isovaline; cross-tolerance; hot plate